Responses of Plasma Catecholamine, Serotonin, and the Platelet Serotonin Transporter to Cigarette Smoking - Lowery, Curtis Lee; Woulfe, Donna; Kilic, Fusun (Frontiers in Neuroscience, 2019)
Thirty percent of all deaths from coronary heart disease in the US are attributable to cigarette smoking. Cigarette smoking produces central nervous system-mediated activation of the sympathetic nervous system, which stimulates secretion of serotonin (5-HT) and catecholamines to supraphysiological levels in blood. The enhanced levels of 5-HT and catecholamines in smokers’ blood are associated with increases in G protein-coupled receptors signaling and serotonylation of small GTPases, which in turn lead to remodeling of cytoskeletal elements to enhance granule secretion and promote unique expression of sialylated N-glycan structures on smokers’ platelets. These mechanisms enhance aggregation and adhesion of smokers’ platelets relative to those of non-smokers. This review focuses on the known mechanisms by which 5-HT and the coordinate signaling of catecholamines impacts cigarette smokers’ platelet biology.